2022
DOI: 10.3390/insects13090808
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Weathering Time by the Empty Puparium of Sarcophaga peregrina (Diptera: Sarcophagidae) with the ANN Models

Abstract: Empty puparium are frequently collected at crime scenes and may provide valuable evidence in cases with a long postmortem interval (PMI). Here, we collected the puparium of Sarcophaga peregrina (Diptera: Sarcophagidae) (Robineau-Desvoidy, 1830) for 120 days at three temperatures (10 °C, 25 °C, and 40 °C) with the aim to estimate the weathering time of empty puparium. The CHC profiles were analyzed by gas chromatography-mass spectrometry (GC-MS). The partial least squares (PLS), support vector regression (SVR),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…MSD ChemStation Data Analysis F.01.03 was used to integrate the peak height, and only compounds with a consistent peak height percentage above 0.5% were included. Hydrocarbons were identified using a library search (NIST14), the Kovats Index based on external standards, and literature [49].…”
Section: Cuticular Hydrocarbons (Chcs) Analysismentioning
confidence: 99%
“…MSD ChemStation Data Analysis F.01.03 was used to integrate the peak height, and only compounds with a consistent peak height percentage above 0.5% were included. Hydrocarbons were identified using a library search (NIST14), the Kovats Index based on external standards, and literature [49].…”
Section: Cuticular Hydrocarbons (Chcs) Analysismentioning
confidence: 99%
“…We found that the compound classes of hydrocarbons increased with the increases in temperature from 20 °C to 30 °C, and the percentage composition of long-chain hydrocarbons, such as C24, decreased regularly with the pupal development of S. peregrina . It might be that higher temperatures increased biodegradation and accelerated the weathering of the surface pupal cuticle, leading to an increase in the CHCs in pupae [ 31 ]. In addition, we found that the separation between the age classes from CHC analysis in Figure 3 is better with increasing temperatures from 20 °C to 30 °C and shows a clear separation at 30 °C.…”
Section: Discussionmentioning
confidence: 99%
“…A supervised statistical method of discriminant analysis was performed using orthogonal partial least squares discriminant analysis (OPLS-DA) [ 31 ]. Multivariate regression using partial least squares (PLS) is a common statistical technique [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations